The Transcription Axes ERK-Elk1, JNK-cJun, and JAK-STAT Promote Autophagy Activation and Proteasome Inhibitor Resistance in Prostate Cancer Cells - Georgios Kalampounias; Kalliopi Zafeiropoulou; Theodosia Androutsopoulou; Spyridon Alexis; Argiris Symeonidis; Panagiotis Katsoris (Current Issues in Molecular Biology)
The rapid emergence of resistance limits the application of proteasome inhibitors against solid tumors, despite their effectiveness in the treatment of hematological malignancies. Resistant phenotypes are complex and multifaceted, and, thus, the mechanisms involved have not been adequately described. In this study, a Bortezomib-resistant prostate cancer cell line is created by using the PC-3 cell as a prostate carcinoma model of high metastatic potential. The main biochemical differences and adaptations exhibited by the resistant cells revolve around apoptosis evasion, autophagy induction (functioning as a ubiquitin-proteasome system substitute), expression of epithelial-to-mesenchymal transition markers, and increased aggressiveness. Broad-spectrum signaling pathway analyses also reveal an upregulation and activation of Nf-κB, STAT3, cJun, and Elk1 transcription factors in the resistant cells. Additionally, intracellular reactive oxygen species assays reveal a downregulation in resistant cells, which is theorized to be a consequence of metabolic changes, increased autophagic flux, and antioxidative enzyme action. These findings expand our understanding of proteasome inhibitor resistance and highlight key kinases and transcription factors as novel potential therapeutic targets. Effective inhibition of resistance-specific pathways could re-sensitize the cells to proteasome inhibitors, thus surpassing current therapeutic limitations.